Influence of hemostatic solution on bond strength and physicochemical properties of resin cement - de Araújo, Isabela Sousa; do Prado, Célio Jesus; Raposo, Luís Henrique Araújo; Soares, Carlos José; Zanatta, Rayssa Ferreira [UNESP]; Torres, Carlos Rocha Gomes [UNESP]; Ruggiero, Reinaldo; da Silva, Gisele Rodrigues (FapUNIFESP (SciELO), 2017)
The aim of this study was to evaluate the degree of conversion, color stability, chemical composition, and bond strength of a light-cured resin cement contaminated with three different hemostatic solutions. Specimens were prepared for the control (uncontaminated resin cement) and experimental groups (resin cement contaminated with one of the hemostatic solutions) according to the tests. For degree of conversion, DC (n = 5) and color analyses (n = 10), specimens (3 mm in diameter and 2 mm thick) were evaluated by Fourier transform infrared spectroscopy (FTIR) and CIELAB spectrophotometry (L*, a*, b*), respectively. For elemental chemical analysis (n = 1), specimens (2 mm thick and 6 mm in diameter) were evaluated by x-ray energy-dispersive spectroscopy (EDS). The bond strengths of the groups were assessed by the microshear test (n = 20) in a leucite-reinforced glass ceramic substrate, followed by failure mode analysis by scanning electron microscopy (SEM). The mean values, except for the elemental chemical evaluation and failure mode, were evaluated by ANOVA and Tukey’s HSD test. The color stability was influenced by storage time (p<0.001) and interaction between contamination and storage time (p<0.001). Hemostop and Viscostat Clear contamination did not affect the DC, however Viscostat increased the DC. Bond strength of the resin cement to ceramic was negatively affected by the contaminants (p<0.001). Contamination by hemostatic agents affected the bond strength, degree of conversion, and color stability of the light-cured resin cement tested.
Keywords: Bond strength; Color analysis; Degree of conversion; Hemostatic solutions; Light-cure resin cement